2012
DOI: 10.12669/pjms.291.2910
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of congenital heart disease in children admitted for cardiac surgery at Rehman Medical Institute, Peshawar, Pakistan

Abstract: Objective: To assess age, gender distribution and relative frequency of congenital heart disease (CHD) in children who underwent palliative or corrective cardiac surgery at Rehman Medical Institute, Peshawar. Methodology: This retrospective study was conducted in Department of Cardiac Surgery at Rehman Medical Institute (RMI), Peshawar from May 2008 till May 2010. One hundred and twenty three patients up to age group of 16 years with confirmed diagnosis of congenital heart disease admitted for Cardiac Surgery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 11 publications
3
17
0
Order By: Relevance
“…The high PDA prevalence in our cohort could be explained by the fact that 70% of our PDA diagnosed infants were premature. High rate of PDA has been also reported in Pakistan (19) and India (20). Some studies excluded PDA from CHD unless they are hemodynamically significant while others included PDA only if it persisted beyond certain age, and this explains the big variation in the reported rate of PDA.…”
Section: Discussionmentioning
confidence: 99%
“…The high PDA prevalence in our cohort could be explained by the fact that 70% of our PDA diagnosed infants were premature. High rate of PDA has been also reported in Pakistan (19) and India (20). Some studies excluded PDA from CHD unless they are hemodynamically significant while others included PDA only if it persisted beyond certain age, and this explains the big variation in the reported rate of PDA.…”
Section: Discussionmentioning
confidence: 99%
“…Also in Pakistan, 123 patients between the ages of 1-16 years had cardiac surgery for the period of 2008-2010. In their study, the males were 71 (57.7%) and females were 52 (42.3%) with a ratio of 1.3:1 [27]. That is to say that cardiac diseases are commoner in males than females.…”
Section: Discussionmentioning
confidence: 88%
“…In NCTCE, Korlebu, Accra Ghana, in 464 cases done between, 1996 and 2008, 25% were intra-cardiac operations while 75% were extra cardiac operations [20]. In India, the work of Zahid et al comparing CHD and acquired heart disease, among 150 children below six years that had cardiac surgery, it showed that congenital heart defect constituted 89.3% while acquired heart disease was 10.7% [27]. In this same study, acyanotic heart defect was 74.6% with VSD (29.9%) and ASD (25.4%), while cyanotic heart defect was 23.9% with TOF being 11.2%.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] Tricuspid atresia is an example of a cyanotic CHD characterized by the absence of the tricuspid valve, which blocks the blood flow from the right atrium to the ventricle. [ 2 ] An example of acyanotic CHD is the atrial septal defect, which is opened into the remnant of foramen ovale, causing the blood to flow between the atria. [ 2 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] An example of acyanotic CHD is the atrial septal defect, which is opened into the remnant of foramen ovale, causing the blood to flow between the atria. [ 2 ]…”
Section: Introductionmentioning
confidence: 99%